Multilayer Super-Translucent Zirconia for Chairside Fabrication of a Monolithic Posterior Crown - Sven Rinke; Anna Metzger; Holger Ziebolz (Case Reports in Dentistry)
This case report describes the chairside fabrication of a monolithic posterior crown using a multilayer super-translucent zirconia material. According to the manufacturer’s information, the newly introduced multilayer zirconia (4-YTZP) offers a unique combination of fracture strength (>850 MPa with speed-sintering) and improved optical properties, thus allowing a reduced minimum material thickness and optional temporary luting. By using up-to-date components of the CEREC system, including superfast dry-milling and a speed-sintering process, the fabrication of a monolithic zirconia crown is possible within an acceptable timeframe for the chairside workflow (60-75 min). The usage of a multilayer super-translucent material allows for the individualization of the restoration, typically in a single combined stain and glaze firing. However, it should be noted that clinical data for this type of restoration are still sparse. Therefore, manufacturer recommendations regarding indication, preparation, and cementation must be followed very strictly.